Phytoindication assessment of the lighting mode as a marker of regulatory ecosystem services in tehnosoil of Nikopol manganese ore basin - Маслікова, К. П.; Жуков, О. В.; Коваленко, Д. В. (Scientific Progress & Innovations, 2018)
The research shows the possibility of indication of the regulatory ecosystem services for man-made soilogenesis by means of phytoindication using lighting indicator scale. Field studies were conducted during the 2008–2017 in bioecological research station in Dnipro agro-economic University (Pokrov, Dnipropetrovsk region, Ukraine). Polygons incorporated within tehnosoils four types: pedozems, sod-lithogenic soils on forest-like loam, gray-green clay and red-brown clay. Vegetative mass distribution of individual components of complex multi agrophytocenoses, mutual influence aboveground components of each other and environmental conditions under the canopy of vegetation have a significant effect on yield formation of plant communities. A more uniform distribution of leaf blades in phytocenoses weakening lighting at the middle and lower tiers won’t be very large. It causes the highest intensity operation vegetation photosynthesis per unit area. In order embriozemy → sod soils lithogenic → pedozemy level assessment phytoindication lighting statistically significantly reduced. Herbaceous vegetation that covers most forms of tehnosoils is formed in the global lighting. Vegetation of the embriozems lighting mode indicates 8.78±0.01, sod soils lithogenic – 8.74±0.02, pedozems – 8.71±0.01.